2015
DOI: 10.1021/nn5070953
|View full text |Cite
|
Sign up to set email alerts
|

High Relaxivity Gd(III)–DNA Gold Nanostars: Investigation of Shape Effects on Proton Relaxation

Abstract: Gadolinium(III) nanoconjugate contrast agents (CAs) have distinct advantages over their small-molecule counterparts in magnetic resonance imaging. In addition to increased Gd(III) payload, a significant improvement in proton relaxation efficiency, or relaxivity (r1), is often observed. In this work, we describe the synthesis and characterization of a nanoconjugate CA created by covalent attachment of Gd(III) to thiolated DNA (Gd(III)–DNA), followed by surface conjugation onto gold nanostars (DNA–Gd@stars). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 73 publications
7
142
0
Order By: Relevance
“…The loading of Lip-DO3A@AuNP and Lip-DTPA@AuNP represents greater than a 3- and 2-fold increase in Gd(III) payload and packing density, respectively, relative to previously reported DNA-Gd@AuNP (564 Gd(III)/AuNP and 0.8 Gd(III)/nm 2 of AuNP). 12 This phenomenon is attributed to the efficient packing of small molecular Gd(III) chelates relative to polyvalent DNA-Gd(III) conjugates on the surface of the AuNP.…”
Section: Resultsmentioning
confidence: 99%
“…The loading of Lip-DO3A@AuNP and Lip-DTPA@AuNP represents greater than a 3- and 2-fold increase in Gd(III) payload and packing density, respectively, relative to previously reported DNA-Gd@AuNP (564 Gd(III)/AuNP and 0.8 Gd(III)/nm 2 of AuNP). 12 This phenomenon is attributed to the efficient packing of small molecular Gd(III) chelates relative to polyvalent DNA-Gd(III) conjugates on the surface of the AuNP.…”
Section: Resultsmentioning
confidence: 99%
“…132 Recently, Rotz et al . described the surface conjugation of DNA–Gd onto gold nanostars and nanospheres 95 and found that DNA–Gd@stars exhibited remarkable r 1 values up to 98 mM −1 s −1 , much higher than those of DNA–Gd@spheres, where r 1 values were 25 times larger than FDA-approved Gd chelates at 25 °C (Fig. 14a and b).…”
Section: Factors Influencing Relaxivity Of Mri Contrast Agentsmentioning
confidence: 99%
“…Furthermore, these nanostructured Gd(III) agents present enhanced relaxivity compared with free Gd(III) chelates due to both cumulative effect of the high number of Gd(III) ions per nanocarrier and the reduced global tumbling motion that enhance the r 1 of each nanocomplex (10,(15)(16)(17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…We can infer from this increased relaxivity that the presence of PEG molecules on the surface of the nanoparticles facilitates the approach of water protons to the NM surface, closer to the internally encapsulated Gd(III) ions, and reduces the mobility of the nanocomplex. The diffusion of water in the proximity of the Gd(III) is known to play an important role in the enhancement of proton relaxivity (19,29,(41)(42)(43). Besides Gd(III) concentration and surface functionalization, temperature can also affect the relaxivity, which can have a major impact in vivo (33).…”
Section: Significancementioning
confidence: 99%